Pengaruh Ekowisata Curug Cileat dalam Meningkatkan Perekonomian Masyarakat - Nugraha, Rijaludin; Safei, Agus Ahmad (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
Ecotourism is a concept of ecosystem-based community development. Therefore, a region needs to pay attention to its strategic sectors to support its region. This study aims to determine how much influence Curug Cileat tourism has on the economic income of the community in Kampung Cibago in terms of community roles, tourism management and the results achieved from tourism development. This research uses qualitative or descriptive methods. Data collection was carried out by direct observation to the Cileat waterfall tourist spot, interviews with 20 respondents. The results of the research show that: the community plays a significant rolein building and maintaining ecotourism. The management of Cileat is currently being coordinated by Perhutani, which is mandated by Mr. Amartajudin. Success in maintaining and developing ecotourism is getting better as measured by the increasing number of tourists, income and the level of the community's economy.